(3GdSjGSGJ GdfbOjI hGdHYO GdOhdj ddjhQh (B/s - (3eUWai, CMeO aQjOs; (3MSf, SejQ eMeO GdSjO s ((3GdGScfOQjI(B: s (3eDSSI THGH GdLGeYI(B, s, 2000)
(3GdCfXeI hGdSjGSGJ GdfbOjI(B-(3eaghe GdSjGSI GdfbOjI hCOhGJgG(B-(3GdSjGSGJ GdfbOjI aj GbJUGO GSdGej ebGHd GdEbJUGO GdhVYj(B-(3CKQ GdSjGSI GdfbOjI Ydi GdeJZjQGJ GdGbJUGOjI(B-(3YdGbI GdSjGSI GdfbOjI Ydi GdeJZjQGJ GdGbJUGOjI(B-(3YdGbI GdSjGSI GdfbOjI HGdSjGSI GdGbJUGOjI(B-(3GdYedGJ GdeMhQjI hCReI GdOhdGQ aj GdaJQI ef (B1968(3Edi (B1974-(3GdSjGSI GdeGdjI ddOhdGQ(B-(3CKQ GQJaGY SYQ GdOhdGQ Ydi GdGbJUGO GdeUQj(B-(3GdJMhd Edi GdYedI GdGhQhHjI GdehMOI hGdHYO GdOhdj ddjhQh(B1999s
(3HHdhZQGajG(B: (3U(B.283s
Keywords: (3GdSjGSI GdfbOjIs; (3GdfbhOs; (3GdjhQhs